Diversity, spatial distribution and evolution of inactive and weakly active hydrothermal deposits in the TAG hydrothermal field - Pelleter, Ewan-Loiz; Principaud, Mélanie; Alix, Anne-Sophie; Boissier, Audrey; Cheron, Sandrine; Besson, Florian; Altorffer, Vincent; Guérin, Charline; Gaillot, Arnaud; Pierre, Delphine; Rospabé, Mathieu; Giunta, Thomas; et al. (Frontiers in Earth Science, 2024)
Introduction: Although, there is an increasing focus on inactive or extinct seafloor massive sulfide (SMS) deposits driven by the possibility of marine mining, only few studies have been devoted to them so far. The Trans-Atlantic Geotraverse (TAG) hydrothermal field is probably one of the best-studied hydrothermal systems even if the relict SMS deposits known since the mid-1980s have not been thoroughly explored. Objectives: The main objective of this study was to describe the characteristics of these so-called inactive sites. Methods: During four different expeditions, we acquired high-resolution acoustic data and performed numerous human occupied vehicle (HOV) dive operations including extensive rock sampling and in-situ temperature measurements. Results and Discussion: We discovered thirteen new hydrothermal mounds including six large (i.e. > 5,000 m2) deposits making the TAG hydrothermal field one of the largest accumulation of hydrothermal materials (21.1 Mt) known on the seafloor. However, copper and zinc grades of the largest SMS deposits remain low (i.e. < 1.4 wt%) even compared to on-land volcanogenic massive sulfide deposits. Additionally, eight areas of diffuse hydrothermal fluid flow were identified challenging the presumed inactivity of these SMS deposits and, for the first time, emphasizing the importance of low temperature (LT) hydrothermal activity in whole the TAG field. Inactive and weakly active SMS deposits exhibit a large diversity of surface mineralization (e.g. sulfides, Fe-Mn mineralization, jasper) illustrating complexity of hydrothermal activities but also different ageing history. Several mounds no longer have visible sulfide chimneys and are covered by a widespread layer of manganese and iron oxyhydroxides attesting the longevity of diffuse fluid flow at specific locations even long after last high-temperature (HT) hydrothermal activity has ceased. This contrasts with SMS deposits that are devoid of extensive LT precipitates but characterized by standing or topped sulfide chimney indicating a relatively abrupt cessation of HT hydrothermal activity. Conclusion: Together these results allow us to propose evolution models to explain the diversity of active, weakly active and inactive SMS deposits in the TAG hydrothermal field.